"A Study on the Effectiveness of Inquiry-Based Science Teaching in India: Student-Centric Models for Enhanced Learning" (International Journal of Food and Nutritional Sciences, 2021)
This research investigates the efficacy of scientific instruction for student learning using an inquiry approach, paying rather special attention to the responsiveness of students and learning outcomes. Accordingly, the study employs a mixed-methods analysis based on secondary data from multiple studies of the adoption of inquiry-based teaching by preservice teachers, teachers’ opinions of the switch to this kind of teaching, and the relative efficacy of inquiry versus traditional teaching methods. The results indicate that inquiry-based teaching leads to significantly (25%) greater student achievement (Cohen's d = 1.42) relative to traditional lectures. The research points out crucial variables that affect the uptake of inquiry-based approaches (i.e., administrative assistance and teacher preparation). While inquiry-based learning is preferred by 60 percent of educators, issues, such as incomplete adoption patterns, and concerns about job security remain. The results show the importance of teacher preparation courses and institutional support provided for inquiry-based approaches to work successfully. By adding to the existing discussions on educational reform in India, this study supports creative teaching methods that emphasize student participation and active learning in scientific education.